2014
DOI: 10.4314/ahs.v13i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Care of terminally-ill patients: an opinion survey among critical care healthcare providers in the Middle East

Abstract: Background: Modern medicine has allowed physicians to support the dying terminally-ill patient with artificial means. However, a common dilemma faced by physicians in general, and intensivist in particular is when to limit or withdraw aggressive intervention. Objective: To study the effect of training background and seniority on Do-not to resuscitate (DNR) decisions in the Middle East. Methods: Anonymous questionnaire sent to members of the Pan Arab Society of Critical Care. Results: The response rate was 46.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 13 publications
1
36
1
Order By: Relevance
“…In a survey among critical care health-care providers in the Middle East, 46.5% of responders expressed their concern that patients were likely to be clinically neglected once labeled as DNR. 29 Stevenson et al 30 showed that residents appear to assume that patients with DNR orders would prefer not to receive other interventions, so potentially beneficial care may be withheld against the patient's wishes. Beach et al 31 found that the presence of a DNR order may affect a physician's willingness to order a variety of interventions/treatments not related to CPR (such as taking blood cultures, putting in a central line, or referral to an ICU).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey among critical care health-care providers in the Middle East, 46.5% of responders expressed their concern that patients were likely to be clinically neglected once labeled as DNR. 29 Stevenson et al 30 showed that residents appear to assume that patients with DNR orders would prefer not to receive other interventions, so potentially beneficial care may be withheld against the patient's wishes. Beach et al 31 found that the presence of a DNR order may affect a physician's willingness to order a variety of interventions/treatments not related to CPR (such as taking blood cultures, putting in a central line, or referral to an ICU).…”
Section: Discussionmentioning
confidence: 99%
“…These differences were significant after controlling for religious importance and attendance (Wolenberg et al, 2013), and the least religious physicians were less likely to oppose withholding or withdrawing ANH. Another study showed that the majority of Muslim physicians in the Middle East believe in feeding DNR patients (ur Rahman et al, 2013). …”
Section: Artificial Nutrition and Hydration (Anh) And Pain Managementmentioning
confidence: 99%
“…More than half of Muslim physicians surveyed in the Middle East consider the ability to pray an extremely important aspect of EoL care (ur Rahman et al, 2013). However, Khalid et al (2013) found that there is minimal involvement of Muslim chaplains or social workers in EoL discussions in the region.…”
Section: Miscellaneous (Table 4)mentioning
confidence: 99%
“…Usually, DNR decisions are ordered by the physicians, but a study in Denmark suggested that the physicians and the patients should make the final decisions together. [7] In Saudi Arabia, there is Islamic Fatwa which is considered to be an essential part decision-making process because different systems and the authorities in Saudi Arabia follow the Islamic law. The Islamic opinion on DNR was published in 1988.…”
Section: Introductionmentioning
confidence: 99%